2020
DOI: 10.1088/1757-899x/1001/1/012115
|View full text |Cite
|
Sign up to set email alerts
|

Hazards and occupational risk assessment in the bricklayer’s workplace

Abstract: The purpose of the research – hazard analysis and calculation of the level of occupational risk at the bricklayer’s workplace. The scientific task that was solved in the course of the study was the analysis of the dangers associated with each other by various technological processes during stone work. The result of the study is to determine the level of professional risk by the method of a three-level scale of damage based on the analysis of the main characteristics. For this study, the main hazards in the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The assessment of occupational risk by the proposed method makes it possible to identify the most significant groups of risk-forming factors in terms of the impact of working conditions in the workplace. The obtained values are compared with the results ranking scale, the values of which correspond to the values of the five-level damage scale and range from very low to very high [2,14]. Based on the calculations and assessments carried out, appropriate measures are being developed to reduce the impact of occupational risk in the workplace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of occupational risk by the proposed method makes it possible to identify the most significant groups of risk-forming factors in terms of the impact of working conditions in the workplace. The obtained values are compared with the results ranking scale, the values of which correspond to the values of the five-level damage scale and range from very low to very high [2,14]. Based on the calculations and assessments carried out, appropriate measures are being developed to reduce the impact of occupational risk in the workplace.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of existing methods has shown that, despite all the diversity, a single approach to assessing occupational risks has not been established and they are not always applicable in practice [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Kazachy Erik, improvement of water exchange, improvement of the state of the feeding and reproduction value of water bodies, restoration of the disturbed natural hydrological regime of the river. Kazachy Erik, improving the sanitary and fishery state of water bodies, as well as preventing the flooding of adjacent lands in the event of an emergency [9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for assessing and managing occupational risks is one of the main elements of the organisation's occupational safety management system, which is aimed at ensuring the safety and health of employees. The Regulation on the occupational health and safety management system states that the methods of assessing occupational risks are determined by the employer independently [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%